2021
DOI: 10.1182/blood-2021-152603
|View full text |Cite
|
Sign up to set email alerts
|

Nanatinostat (Nstat) and Valganciclovir (VGCV) in Relapsed/Refractory (R/R) Epstein-Barr Virus-Positive (EBV +) Lymphomas: Final Results from the Phase 1b/2 VT3996-201 Study

Abstract: Introduction: EBV can be associated with several types of lymphomas, with reported frequencies of up to 8-10% in diffuse large B cell lymphoma (DLBCL), 30-100% in peripheral T cell lymphoma (PTCL) subtypes, 80% in post-transplant lymphoproliferative disease (PTLD), and 15-30% in classical Hodgkin lymphoma (HL), with adverse impact on outcomes. Nanatinostat (Nstat) is a Class-I selective oral HDAC inhibitor that induces the expression of the lytic BGLF4 EBV protein kinase in EBV + tumor cells, activating gancic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 0 publications
0
30
0
Order By: Relevance
“…Clinical support for combining an HDACi with an antiviral drug was initially provided by a Phase 1/2 proof‐of‐concept study conducted with the pan‐HDACi, arginine butyrate, in combination with ganciclovir in patients with recurrent EBV+ B‐cell lymphomas, which demonstrated significant anti‐tumor activity (4 CR and 6 PR) among 15 patients treated 91 . Final Results from the Phase 1b/2 VT3996‐201 study of the combination of nanatinostat and valganciclovir in relapsed/refractory EBV+ lymphomas were presented at the 2021 ASH annual meeting in Atlanta, GA 92 . As of June 2021, 55 patients were enrolled and 43 patients were evaluable for response.…”
Section: Management Of Ebv+ Dlbcl Nosmentioning
confidence: 99%
“…Clinical support for combining an HDACi with an antiviral drug was initially provided by a Phase 1/2 proof‐of‐concept study conducted with the pan‐HDACi, arginine butyrate, in combination with ganciclovir in patients with recurrent EBV+ B‐cell lymphomas, which demonstrated significant anti‐tumor activity (4 CR and 6 PR) among 15 patients treated 91 . Final Results from the Phase 1b/2 VT3996‐201 study of the combination of nanatinostat and valganciclovir in relapsed/refractory EBV+ lymphomas were presented at the 2021 ASH annual meeting in Atlanta, GA 92 . As of June 2021, 55 patients were enrolled and 43 patients were evaluable for response.…”
Section: Management Of Ebv+ Dlbcl Nosmentioning
confidence: 99%
“…Lytic cycle induction using the histone deacetylase inhibitor nanatinostat in combination with the antiviral agent valganciclovir has also been attempted at targeting relapsed/refractory EBV-positive ENKTL [ 59 ]. Antiviral agents such as ganciclovir require the presence of functional viral thymidine kinase, BGLF4, a lytic phase protein, for activation [ 111 ].…”
Section: Targeting Ebv In the Treatment Of Enktlmentioning
confidence: 99%
“…Antiviral agents such as ganciclovir require the presence of functional viral thymidine kinase, BGLF4, a lytic phase protein, for activation [ 111 ]. Nanatinostat induces the expression of BGLF4 EBV protein kinase in EBV-positive tumor cells, activating ganciclovir (GCV) via phosphorylation [ 59 ]. The Phase 1b/2 VT3996-201 study combined nanatinostat with vanganciclovir for treatment of histologically confirmed EBV-positive lymphomas relapsed/refractory after at least one prior systemic therapy [ 99 ].…”
Section: Targeting Ebv In the Treatment Of Enktlmentioning
confidence: 99%
See 1 more Smart Citation
“…BGLF4 can, in turn, activate anti-viral agent Ganciclovir by phosphorylation, making EBV-infected cells susceptible to anti-viral treatment [ 92 ]. A phase 1b/2 VT3996-201 study combined the HDAC inhibitor nanatinostat with valganciclovir for the treatment of histologically confirmed EBV-positive r/r lymphomas [ 68 ]. The study enrolled a total of 15 T/NK non-Hodgkin lymphoma subjects: 5 PTCL-NOS, 1 cutaneous T-cell lymphoma, and 9 extranodal NK-/T-cell lymphoma patients.…”
Section: Additional Approachesmentioning
confidence: 99%